افسانہ " بازیافت " اور دو بہنیں" کا نفسیاتی تجزیہ - نیلم گوہر; ڈاکٹر انور علی (Khayaban - خیابان, 2024)
Psychology is a vast and fascinating science. It is a branch of philosophy. The best writer is one who is familiar with psychology of the characters they have crafted. Psychology is a science that studies the behavior of an individual in their environment. The expert in psychology, “Sigmund Freud”, first gave it scientific status through the analysis of psychoanalysis, laying the foundation of modern psychology. Psychological complexities include pride, superiority, inferiority, sexual suppression, or any abnormal condition; if they cannot find a means of expression, the individual may suffer from various mental disorders. One of the perspectives in psychology is narcissism. Narcissism is a psychological term with its fundamental concept based on self-love and self-worship. Psychologists derived this term from Greek mythology, with Narcissus as the central character. Praim Chand was the first social realist in Urdu literature. His stories have been studied from various perspectives, but it is important to analyze them from a psychological context. This article discusses the stories "دو بہنیں" (Two Sisters) and " بازیافت" (Recovery)" in the context of narcissism. In these stories, elements of false ego, competition, misperception, self-love, and self-advertisement, among other narcissistic traits, are evident.